Prospects of Asean Legal Cooperation - Agus Riyanto (Bina Nusantara University, 2016)
Association of Southeast Asian Nations (ASEAN) is a regional organization in the countries of Southeast Asia established in Bangkok, Thailand, on August 8, 1967 (the Bangkok Declaration) by Indonesia, Malaysia, Philippines, Singapore, and Thailand. One form of cooperation that could further encourage the establishment of ASEAN's goal was legal cooperation. This was because, this cooperation could further strengthen cooperation in politics, economy, social and culture in Southeast Asia. This paper aimed to identify and learn how the real prospect of legal cooperation could be realized. Therefore, it should be known that areas of cooperation of the law which allows conducted cooperation among ASEAN countries use sectoral laws as an alternative legal cooperation. Method of this paper was comparative law in the ASEAN countries due to the countries in Southeast Asia have different legal systems. The result of this paper is the prospects of ASEAN legal cooperation is very open to be realized, because the settings are clear legal basis exists and regulated. Just to get to the realization of such cooperation, the ASEAN countries must have a strong political will to become solid cooperation.